A polysaccharide-based hydrogel platform for tumor spheroid production and anticancer drug screening - Elliot Lopez-Vince; Teresa Simon-Yarza; Claire Wilhelm (Scientific Reports)
Abstract Extracellular matrix mimics are still needed to grow cancer cells in 3D environments and study their evolution in vitro while precisely controlling relevant features. Most models currently use collagen, which is biomimetic but degrades quickly, or artificial polymers, which can be chemically modified but remain stiff. Herein we introduced a soft, non-adhesive, and resistant hydrogel platform for tumor spheroid production using a polysaccharide-based formulation. To ensure micro-structuring of the hydrogel and enable spheroid formation, 3D printed molds consisting of a network of 200-µm-diameter micropillars were used to generate microstructured hydrogel constructs that fit into a multi-well plate. This platform was validated for drug testing using three cancer cell lines (A673, MCF7 and U87) and 2 anticancer drugs (doxorubicin and paclitaxel). Drug response was assessed through bright-field microscopy monitoring and viability measurements after 48 h of treatment. This study validates the use of pullulan-dextran hydrogels for spheroid formation, combined with in situ drug screening.